2015
DOI: 10.3171/2015.1.peds14407
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcomes of radiosurgery for arteriovenous malformations in pediatric and adolescent populations

Abstract: OBJECT Although stereotactic radiosurgery (SRS) has been accepted as a therapeutic option for arteriovenous malformations (AVMs) in children and adolescents, substantial data are still lacking regarding the outcomes of SRS for AVMs in this age group, especially long-term complications. This study aimed to clarify the long-term outcomes of SRS for the treatment of AVM in pediatric patients aged ≤ 18 years. METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 49 publications
2
16
0
1
Order By: Relevance
“…Despite advancement of techniques in AVM manage- ment, the risk of hemorrhage persists after treatment and is reported to be 1.4% overall per patient per year in the general patient population. 48 In regard to pediatric patients with AVMs, this rate is 0.3%-4.3% for patients who underwent radiosurgery, 2,3,8,9,17,21,29,37,42,43,54,56,57 and 0%-0.3% for patients after resection. 8,16,50 To the best of our knowledge, this is the first study attempting to compare posttreatment hemorrhagic risk across different treatment modalities in a single cohort of pediatric patients with AVMs.…”
Section: Discussion Hemorrhagic Risk Of Avmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advancement of techniques in AVM manage- ment, the risk of hemorrhage persists after treatment and is reported to be 1.4% overall per patient per year in the general patient population. 48 In regard to pediatric patients with AVMs, this rate is 0.3%-4.3% for patients who underwent radiosurgery, 2,3,8,9,17,21,29,37,42,43,54,56,57 and 0%-0.3% for patients after resection. 8,16,50 To the best of our knowledge, this is the first study attempting to compare posttreatment hemorrhagic risk across different treatment modalities in a single cohort of pediatric patients with AVMs.…”
Section: Discussion Hemorrhagic Risk Of Avmsmentioning
confidence: 99%
“…35 In comparison, in a radiosurgical cohort of 116 pediatric patients with AVMs reported recently by Hanakita et al, only 10 patients were reported to develop adverse events, rendering a 91.4% optimal functional outcome, with prior AVM hemorrhage showing marginal association with worse functional outcomes. 17 In a more comprehensive analysis presented by Darsaut et al, where all major modalities were included, the overall proportion of patients achieving good functional outcomes was 74.2%, in which high grade, left side, and poor baseline mRS score were significant predictors in the multivariate analysis. 8 These data are largely consistent with those in our study.…”
Section: Functional Outcomes In Pediatric Patients With Avmsmentioning
confidence: 96%
“…Although the short-term risks of SRS are known to be generally less frequent than those associated to other treatment modalities, the longer, continuous risks of radiation, which may occur even >10 years after treatment, remain unclarified, 20 with its accumulated risks, based on follow-up periods of >20 years, still largely unknown. To definitively determine the clinical benefits of SRS for small unruptured AVM, prospective studies with such long follow-up periods are needed.…”
Section: Strokementioning
confidence: 99%
“…Initially, only biplanar digital subtraction angiography (DSA) was used; however, owing to modern advances in radiological techniques and the development of planning software, CT angiography (CTA) and MRI have become valuable tools, as they enable axial image-based radiosurgical planning, which improves the quality of target contouring. 4,17,20,21,24 Since radiotherapy planning is solely dependent on radiological images, using high-resolution images is essential, as such images can theoretically reduce radiation waste and avoid suboptimal coverage of the targets, ultimately improving the radiosurgical outcome. 12,22 However, the imaging modality best suited to provide high-resolution images for GKS planning remains unknown.…”
mentioning
confidence: 99%